2009
DOI: 10.1152/jn.91110.2008
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Triggers of Skin Conductance Responses and Their Neural Correlates in the Primate Amygdala

Abstract: The amygdala plays a crucial role in evaluating the emotional significance of stimuli and in transforming the results of this evaluation into appropriate autonomic responses. Lesion and stimulation studies suggest involvement of the amygdala in the generation of the skin conductance response (SCR), which is an indirect measure of autonomic activity that has been associated with both emotion and attention. It is unclear if this involvement marks an emotional reaction to an external stimulus or sympathetic arous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(66 citation statements)
references
References 25 publications
4
61
0
1
Order By: Relevance
“…However, given the copious amounts of anecdotal evidence from humans, and the more recent empirical studies supporting the uncanny valley effect in humans (2, 3), it seems parsimonious to conclude that monkeys are also experiencing at least some of the same emotions. To support this notion, future experiments could incorporate somatic markers, such as skin conductance responses, pupil dilation, or facial electromyography, to measure the emotional responses of monkeys to the differently rendered faces from monkeys (17)(18)(19)(20). Neurophysiological and neuroimaging approaches could also be illuminating in this regard.…”
Section: Resultsmentioning
confidence: 99%
“…However, given the copious amounts of anecdotal evidence from humans, and the more recent empirical studies supporting the uncanny valley effect in humans (2, 3), it seems parsimonious to conclude that monkeys are also experiencing at least some of the same emotions. To support this notion, future experiments could incorporate somatic markers, such as skin conductance responses, pupil dilation, or facial electromyography, to measure the emotional responses of monkeys to the differently rendered faces from monkeys (17)(18)(19)(20). Neurophysiological and neuroimaging approaches could also be illuminating in this regard.…”
Section: Resultsmentioning
confidence: 99%
“…the input neural signal for the SCR system) takes place in the interaction amygdala-hippocampus: "Outcome of the specific patterning of the match-mismatch process in the hippocampus/amygdala complex determines the precise constellation of signals to be either routed onward to the hypothalamus or aborted, and shapes the affective response or lack thereof to any stimulus event" (Hadley, 1989, p. 346;Laine et al, 2009;Phelps, 2004). In the amygdala-hippocampus interplay the role of the hippocampus is to detect novelty and unexpectedness of the stimulus (Kumaran & Maguire, 2007a, 2007bVinogradova, 1975).…”
Section: Putative Scenario Of Neural Computations During the Scr Processmentioning
confidence: 99%
“…Few lesion studies have explored retention and extinction (Izquierdo and Murray, 2005;Antoniadis et al, 2009), and early electrophysiological work has addressed changes in affective significance of stimuli (Sanghera et al, 1979;Nishijo et al, 1988). However, recent studies have mainly focused on momentary representations of value: single neurons were shown to code contextual information regarding reward schedules (Sugase-Miyamoto and Richmond, 2005;Bermudez and Schultz, 2010), expectation and state value (Belova et al, 2007), dynamically switch responses with emotional valence (Paton et al, 2006), process facial expressions and identity (Gothard et al, 2007;Kuraoka and Nakamura, 2007), and track the skin-conductance-response (SCR) that reflects emotional state (Laine et al, 2009).…”
Section: Introductionmentioning
confidence: 99%